Understanding global civil society: theory, governance and the global water crisis - Blaney, Dallas S., author; Betsill, Michele Merrill, 1967-, advisor; Chaloupka, William J., 1948-, committee member; Taylor, Peter Leigh, 1959-, committee member; Mumme, Stephen P., committee member (Colorado State University. Libraries, 2010)
How does global civil society (GCS) fit in the history of world politics? Have technology and global capitalism liberated civil society from its former dependence on states and markets to develop into an autonomous and self-regulated sphere within the world political system? If not, perhaps recent developments really signal the emergence of new strategic opportunities for non-state actors to project their domestic political concerns onto the international agenda. Of course, there is also the possibility that GCS primarily functions to reinforce the privileged position of a hegemonic historic bloc, which rests at the confluence of dominant institutions, ideas, and material capabilities. In the effort to answer how GCS fits in the history of world politics, this dissertation identifies and adjudicates the dominant theoretical accounts of GCS. This work rests on the observation that theoretical considerations of GCS have recently entered a new phase. Previously, GCS scholarship worked to build credibility in a field traditionally dominated by a state-centric view of world politics. The success of this initial phase is manifest in the inclusion of GCS into the political lexicon. Thus, what began as an effort to project the concept of GCS outward, in the first phase, turned inward, in the second phase, to weigh the implications of this phenomenon for our understanding of world politics. The specific occasion for this dissertation project is the recent emergence, within the second phase, of three distinct and dominant theoretical positions. The primary goal of this dissertation is to adjudicate these theoretical claims. Thus, this dissertation will appeal to a diverse audience, including international relations scholars, students of global civil society, and water policy experts. At its core this dissertation is concerned with the architecture of the world political system, the changes in this system over time, and the implications of these changes for our understanding of the power relations that both animate and hold this system together - topics that are central to the study of international relations. GCS offers an interesting way to explore these issues, not because its emergence is widely perceived as a new phenomenon in the history of world politics but rather because the very existence of GCS constitutes a potential threat to the core assumption in international relations that states are the dominant central actors within the world political system. For students of GCS, this dissertation offers advice for improving the theoretical development of their burgeoning field. To achieve this end, the dissertation examines the role GCS plays in the global governance of freshwater resources, weighing this evidence against the diverse and divergent theoretical expectations regarding the role GCS plays in the history of world politics. In the process, this analysis highlights the depth and diversity of GCS engagement in the global water crisis, which argues for the need to expand beyond the highly state centric and institutional approach that has thus far consumed the attention of water resource scholars and water policy experts.
Keywords: NGO; global water crisis; global governance; global environmental politics; global civil society; International cooperation; Civil society -- International cooperation; Natural resources -- International cooperation; Water-supply -- Management -- International cooperation